Hubungan antara Drug-Related Problems dan Lama Rawat Inap pada Pasien dengan Diabetes Tipe 2 - Surya Yuli Astuti; Mawardi Ihsan; Fita Rahmawati (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Drug-Related Problems have been associated to blood glucose control along with the morbidity and mortality of type 2 diabetes patients through previous studies. However, studies that associate Length of Stay (LOS) with DRPs in type 2 diabetes patients have not been done. The study that had been done was to associate between LOS and Medication Errors (ME). Medication errors include DRPs because other researchers state that errors are also kind of problem. This study was aimed to identify Drug-Related Problems (DRPs) and to associate between DRPs and LOS in type 2 diabetes patients who were hospitalized. This study was a prospective observation study with a cross-sectional design. Sample collection was carried out by consecutive sampling method in type 2 diabetic patients hospitalized in internal medicine ward in one academic hospital in Yogyakarta. Data analysis was done descriptively to see DRPs description and the association between DRPs and LOS was analyzed using Chi-square or Fisher's exact test whenever Chi-square test conditions were not met. Data collection was carried out in January till April 2018. The results showed that the DRPs in hospitalized type 2 diabetic patients were 80.56% with unnecessary drug therapy occurring at 34.72%; dosage too low of 25%; needs additional drug therapy 13.38%; dosage too high 12.5%; ineffective drug 11.11%; and there was no association seen between DRPs and LOS.